The Analysis and Examination of the Quranic Proofs of the Ruling Ordinances Established by the Supreme Leader in the Exegetical Opinions of Imam Khomeini and Shahid Sadr - Majid Beigi; Ali Karbalaei Pazouki (آموزه‌های قرآنی, 2018)
Imam Khomeini and shahid sadr both have adduced two Quran verses: یَا أَیُّهَا الَّذِینَ آمَنُوا أَطِیعُوا اللهَ وَأَطِیعُوا الرَّسُولَ وَأُولِی الْأَمْرِ مِنْکُمْ and النَّبِیُّ أَوْلَی بِالْمُؤْمِنِینَ مِنْ أَنْفُسِهِمْ and specifically some verses for the authenticity of the ruling ordinances established by the supreme leader. In the thought of Imam Khomeini, the holy prophet has several significant positions: 1. The significance position of the strengthen messenger of God's Ahkam (ordinances). 2. The great position of judgment and judiciary. The holy prophet because of the great position of the prophecy, he is only the messenger of God's ordinances and he himself has no command and forbidding and all his sayings indicate (present) God's orders and commands. Therefore, in the verse أَطِیعُوا اللهَ وَأَطِیعُوا الرَّسُولَ, the obedience of the holy prophet is the obedience of his ruling obedience. With considering that imam Khomeini in his fiqhi and political discourses of the direct faqih involvement in the government (direct faqih ruling) has studied the verses, the Islamic ruler or governor can priories the ruling ordinances over the legal rulings (the legal rules -hukm or ahkam al-shari`ah-) and for وَأَطِیعُوا الرَّسُولَ the believers must obey him. But Shahid Sadr in the fiqhi and political discourses of the restriction of the ruler (ruling) has introduced Mantaqat al-Faraq (the area of separation; the area of the permissible for people). أَطِیعُوا اللهَ obey Allah is in the area of orders which are binding and أَطِیعُوا الرَّسُولَ the obedience of the holy prophet is in the area of orders which are not binding which the holy prophet has ordered based his great position ruling. In his attitude, because of أَولَی بِالْمُؤْمِنِینَ (Surely the Prophet has more superior over the believers), the ruler can make mandatory laws for Muslims. But it is impossible to draw to a close and stop legal rulings (the legal rules -hukm or ahkam al-shari`ah-). Attention to shan-e-nuzool (meaning occasions or circumstances of the revelation) of the verses and the exegetical attitudes and opinions makes the opinion of Imam Khomeini strengthen against the attitudes of Shahid Sadr.